The Potential Use of Actinomycetes as Microbial Inoculants and Biopesticides in Agriculture - Silva, Guilherme da Cruz; Kitano, Isabella Takahashi; Ribeiro, Iron Amoreli de Figueiredo; Lacava, Paulo Teixeira (Frontiers in Soil Science, 2022)
The means of agricultural production are constantly changing, in line with the high demands for productivity that the sector reclaims. The use of fertilizers and chemical pesticides promotes significant improvements in crop development, but some problems and risks associated with them limit their application. An alternative is using biological inputs based on microorganisms, increasing production while combining efficiency and sustainability. Actinomycetes represent important microbial communities in the soils and inhabit a very high proportion of soil microbial biomass that can produce a wide range of high-value antibiotics, organic acids, phytohormones, extracellular enzymes, bioactive compounds, and secondary metabolites other than antimicrobials. Also, actinomycetes play an essential role in biogeochemical cycling and how soils develop. The utilization of actinomycetes for agricultural purposes has increased recently, especially in the biological control of insect-pest and plant disease and in plant growth promotion. Studies report their promising use as microbiological inoculants by exploring mechanisms to promote plant growth, such as biological nitrogen fixation, phosphate solubilization, production of phytohormones, and other biocompounds. In addition, many species produce metabolic pathways that generate toxins against phytopathogens of agricultural importance, with fungicidal, insecticidal, and nematicidal properties. These actinomycetes could be used to formulate novel bioinoculants composed of spores and/or mycelium. Exploring the vast biodiversity of actinomycetes can help develop inoculants and biodefensives, using their potential to search for more productive and conscious agriculture. Research in this field is up-and-coming, with significant economic and environmental impacts in the future.